How Does Replacement of Beef with Agushie Impact the Nutritional and Eating Quality of Beef Burgers? An Observational Approach - W. Y. Akwetey; Z. Ibrahim (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
The research objective was to study the influence of using agushie on proximate composition and eating quality of beef burgers. Meat as a protein rich and carbohydrate “low” product contributes to a low glycemic index which is assumed to be “beneficial” with respect to overweight, the development of diabetes and cancer. Boneless beef was used as the meat ingredient and portions of the beef were replaced with ground agushie at 0% (control), 13%, 26% and 39% to obtain four treatments namely T1, T2, T3, and T4 respectively. Proximate analysis of the burgers was determined as well as cooking yield, pH and sensory evaluation by 30 untrained consumers using a 9-point Hedonic scale. Increasing levels of “agushie” significantly (p<0.05) reduced percentage moisture content from 49.49 (T2) to 46.77 (T4) in the burgers. Crude protein contents increased significantly (p<0.05) from T1 (20.49%) to T4 (27.48%). There were significant (p<0.05) differences in fat content with T2 recording the lowest (12.38%). Ash content also increased significantly (p<0.05) from 2.41% (T1) to 3.77% (T4) while the contents of fibre significantly (p<0.05) increased from 0.24% (T1) to 0.98% (T4). There were also significant differences (p<0.05) in pH (6.14 - 6.55) and cooking yield (60.66%-79.06%) from T1 to T4 respectively. Sensory evaluation revealed no significant (p>0.05) differences across treatments for appearance, taste, flavour, juiciness, texture and acceptability. The results suggest that agushie has beneficial potentials in beef burger production at 26% without any adverse effects on nutritional composition and eating characteristics. It is recommended in future study to determine the influence of agushie on shelf life storage of burgers produced with and without agushie.